Analisis Kepuasan Pelanggan Dengan Metode Importance Performance Analysis Dalam Rangka Meningkatkan Pendapatan Di Agen Distributor Tepung Terigu Wilayah Bekasi Utara (Studi Kasus Di Agen Lestari) - Wahyu Inggar Fipiana; Vivi Lusia; Mohamad Dimas Handoko (Jurnal Manajemen FE-UB, 2021)
Agent Lestari in North Bekasi is one of the service providers for wheat flour distributors inthe North Bekasi area. At this time, measuring customer satisfaction is still managed manually byusing a questionnaire which is also called VOC (Voice of Customer). One of the methods that canbe used to measure customer satisfaction is the servqual method. This method makes acomprehensive assessment of customer satisfaction for services in the service sector. Assessmentis carried out on 5 dimensions of service quality, namely: Reliability or reliability,Responsiveness or responsiveness, Assurance or assurance, Empathy or attention, Tangibles orphysical evidence. Data were obtained from distributing questionnaires to 30 customers of AgenLestari North Bekasi as respondents using simple random sampling technique. This studyobtained a number of 31 attributes of customer needs. Customer data is classified into 8attributes on the reliability aspect, 5 attributes on the responsiveness aspect, 5 on the assuranceattribute, 5 on the empathy dimension, and 8 on the tangibility dimension. Even though theservices provided are not fully as expected, the services of the Lestari Cipinang Agent are goodenough and need to be improved. Customer dissatisfaction arises because of the gap betweencustomer expectations and the reality of perceived performance.Keywords: Quality of Service, Servqual.